Pengembangan Aplikasi AR-Senses Berbasis Augmented Reality sebagai Media Pembelajaran Biologi Sistem Indra Manusia - Dzulqarnain, Muhammad; Isfaeni, Hanum; Rusdi, Rusdi (Universitas Negeri Jakarta, 2025)
Biology is a scientific field that studies living things with a very broad subject matter, one of which is the coordination system material that discusses the human sensory system. Effective and efficient Biology learning process requires the latest digital technology-based learning media such as Augmented Reality. The objectives of this study are 1) to develop Augmented Reality-based AR-Senses application for human sensory system material, 2) to test the feasibility of AR-Senses application as a learning media, 3) to know the response of teachers and students to AR-Senses application. AR-Senses is developed into a Biology learning application that can be run on Android smartphones with the main feature of Augmented Reality and supported by animated video features, short material, and practice quizzes. This research uses the Research and Development (R&D) method with development stages according to the ADDIE model. Data collection used a feasibility validation questionnaire and a response questionnaire to the AR-Senses application. The data analyzed were the results of the feasibility assessment of the AR-Senses application from media experts, material experts, and linguists, as well as the results of responses from Biology teachers and students. The results showed that the AR-Senses application received a media feasibility score of 82%, material feasibility of 82%, language feasibility of 85%, and with an average score of Biology teacher and student trial results of 84.5%, so overall the AR-Senses application received a very feasible category as a learning medium.